2019
DOI: 10.1364/boe.11.000089
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone epifluorescence microscopy for cellular imaging of fresh tissue in low-resource settings

Abstract: Disease diagnosis in low-resource settings can be challenging due to the lack of equipment and trained personnel required for histologic analysis. In this paper, we have developed a smartphone-based epifluorescence microscope (SeFM) for imaging fresh tissues at sub-cellular resolution. SeFM provides similar resolution and field of view (FOV) as those used during histologic analysis. The SeFM device achieved the lateral resolution of 0.57 µm and provided microscopy images over a sample area larger than 500 µm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In vitro internalization in LX22 cells demonstrated the rapid uptake of 123 I-MAPi into LX22 cells. A blocking study with olaparib confirmed target specificity of 123 I-MAPi for PARP1 (Figure 2(A)), a protein whose expression within LX22 cells was confirmed via western-blot (Figure 2(B)) by comparison with FaDu and U251, cell lines known to express PARP1 at detectable levels (Pirovano et al 2019;Kossatz et al 2020;Zhu et al 2020). Subcellular fractionation was performed showing uptake in the membrane, nucleus and chromatin and showed that most of the internalized compound is found in the nucleus and chromatin, with extremely small cytoplasmic localization.…”
Section: Discussionmentioning
confidence: 75%
“…In vitro internalization in LX22 cells demonstrated the rapid uptake of 123 I-MAPi into LX22 cells. A blocking study with olaparib confirmed target specificity of 123 I-MAPi for PARP1 (Figure 2(A)), a protein whose expression within LX22 cells was confirmed via western-blot (Figure 2(B)) by comparison with FaDu and U251, cell lines known to express PARP1 at detectable levels (Pirovano et al 2019;Kossatz et al 2020;Zhu et al 2020). Subcellular fractionation was performed showing uptake in the membrane, nucleus and chromatin and showed that most of the internalized compound is found in the nucleus and chromatin, with extremely small cytoplasmic localization.…”
Section: Discussionmentioning
confidence: 75%
“…The front lens of the camera is easily unscrewed and removed, allowing the optics module to properly function while still providing high-quality imaging. Many lowcost microscopy projects make use of smartphone cameras for imaging [14][15][16], however as these retain the smartphone lens as part of the optical path they usually require additional costly optical components. In contrast, by using a well characterized, widely available sensor (Sony IMX219) [17], the OFM is able to reliably reproduce the reported imaging quality at minimal cost.…”
Section: Imaging Capabilitiesmentioning
confidence: 99%
“…In most cases, indocyanine green fluorescent imaging provides good sensitivity but poor specificity. Molecular contrast agents such as the fluorescent poly(adenosine diphosphate ribose) polymerase inhibitor that are specific to poly(adenosine diphosphate ribose) polymerase 1 might allow rapid and sensitive assays for early tumor detection and accurate assessment of surgical margins in cancer (22), which finds applications also in limited-resources settings (23). Current clinical trials using fluorescence-guided surgery aim to provide results in intraoperative imaging, specimen mapping, pathology correlation, and target validation in a wide variety of studies shown in biomarker expression analysis, laparoscopic NIR imaging, and sentinel lymph node detection (24,25).…”
Section: Clinical Advancesmentioning
confidence: 99%